Silver-ruthenium bimetallic / sio2-zro2 composite carrier catalyst, its preparation method and application
Patent Information
- Application Number
- CN202110601406.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-05-31
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2041-05-31
AI Technical Summary
目前乙醇酸甲酯的传统合成方法有很多,而这些传统工艺中大多存在不足,例如乙二醛与甲醇一步合成法制备MGA,原料中的乙二醛毒性太大,并且价格高,不适用于工业化生产;甲醛与氢氰酸加成法,原料氢氰酸有剧毒,即使收率较高也不适合大规模生产;偶联法,大多采用液体和固体强酸催化,存在严重的腐蚀及反应压力高的缺陷
[0011] One object of the present invention is to provide a bimetallic/composite supported Ag-Ru/SiO2-ZrO2 catalyst with a high specific surface area, which enables the conversion of DMO to MGA at a relatively low reaction temperature when used for the hydrogenation of DMO to MGA. While maintaining high DMO conversion and high MGA selectivity, the catalyst exhibits an ultra-long lifetime.
Smart Images

Figure BDA0003093126690000181
Abstract
Description
Technical Field
[0001] This invention relates to a silver-ruthenium bimetallic / SiO2-ZrO2 composite supported catalyst and its preparation method, and also to a method for preparing methyl glycolate from dimethyl oxalate using the catalyst. Background Technology
[0002] Methyl glycolate (MGA) has a unique molecular structure, combining the chemical properties of both alcohols and esters. It is a chemical urgently needed in the fields of high-end pesticides, pharmaceuticals, chemical engineering, and environmental protection, and is an excellent solvent for the synthesis of cellulose, rubber, and resins. Furthermore, methyl glycolate can undergo carbonylation, hydrolysis, and oxidation reactions, making it an important chemical raw material. Currently, there are many traditional methods for synthesizing methyl glycolate, but most of these processes have shortcomings. For example, the one-step synthesis of MGA from glyoxal and methanol uses glyoxal, which is highly toxic and expensive, making it unsuitable for industrial production. The formaldehyde-hydrogen cyanide addition method uses highly toxic hydrogen cyanide, making it unsuitable for large-scale production even with high yields. Coupling methods mostly employ liquid and solid strong acid catalysis, resulting in severe corrosion and high reaction pressure. Currently, in my country, the hydrolysis and subsequent esterification of chloroacetic acid is commonly used, but this method suffers from severe corrosion, heavy pollution, and limited raw material availability.
[0003] Developing and utilizing my country's abundant coal and natural gas resources, and advancing C1 chemistry, has significant strategic and economic value. Therefore, the production of methyl glycolate from coal has attracted widespread attention. Currently, the technology for producing dimethyl oxalate (DMO) from syngas is relatively mature, and research mainly focuses on the hydrogenation of DMO to prepare MGA.
[0004] Guo Xiangqian et al. (Guangzhou Chemical Industry, Vol. 43, No. 8, 2015-09, pp. 91-93) prepared a CuO-Ag2O / SiO2 solid catalyst supported on silica using a precipitation-deposition method for the hydrogenation of dimethyl oxalate to methyl glycolate. The reaction was carried out at a temperature of 230℃, a pressure of 2.0 MPa, a hydrogen-to-ester ratio of 30:1, and a liquid hourly space velocity of 0.8 h⁻¹. -1 Under the specified conditions, the conversion rate of dimethyl oxalate can reach 92.3%, and the selectivity of methyl glycolate can reach 83.6%. After 500 hours of continuous operation, the conversion rate of dimethyl oxalate stabilizes at around 90%, and the selectivity of methyl glycolate stabilizes at around 80%. However, this catalyst requires a high reaction temperature, and Cu-based catalysts exhibit poor stability at high temperatures; therefore, the catalyst's lifespan has not yet reached the level required for industrial application.
[0005] CN108620107A reports a catalyst for the hydrogenation of dimethyl oxalate to methyl glycolate, its preparation method, and its application. The catalyst uses NiM bi-element particles as the active component and TiO2 as the support; the first element of the NiM bi-element particles is metallic Ni, and the second element M is either non-metallic B or P; the surface area of the TiO2 support is 2-200 m². 2 / g, pore volume 2-200cm³ 3 / g, with a pore size of 0.05-5nm; the catalyst contains 5%-25% Ni and 2%-10% M.
[0006] CN101700496B discloses a catalyst for the hydrogenation of dimethyl oxalate to methyl glycolate and its preparation method. The catalyst has copper as the main active component, silver and manganese as co-active components, and Al2O3 as a support. The copper content is 25% to 50% of the catalyst mass, the silver content is 5% to 15% of the catalyst mass, the manganese content is 8% to 20% of the catalyst mass, and the Al2O3 content is 15% to 40% of the catalyst mass.
[0007] Gong Haiyan et al. (Chemical Reactions and Engineering, Vol. 30, No. 2, 2014-04, pp. 17-23) prepared a copper-supported CuO / SiO2 solid catalyst on silica using the ammonia stripping method for the hydrogenation of dimethyl oxalate to methyl glycolate. Under optimal process conditions of a hydrogen-to-ester ratio of 40–60, a pressure of 2–2.5 MPa, a reaction temperature of 453–473 K, and a space velocity of 0.3–0.7 mg / (g-Cat·h), the conversion of dimethyl oxalate was greater than 80%, and the selectivity for methyl glycolate was greater than 80%. However, the catalyst's activity was not high enough, and its stability was not reported.
[0008] Ouyang Mengyao from Tianjin University (Dissertation, 2016, 5) synthesized hierarchical porous silica nanospheres (KCC-1) as a support via hydrothermal crystallization and prepared an Ag / KCC-1 catalyst using an equal-volume impregnation method. The effect of Ag loading on the catalytic performance of the hydrogenation of oxalate to methyl glycolate was investigated. The study found that when the silver loading was 15%, the catalyst exhibited a higher active silver surface area and therefore better catalytic activity. (The text abruptly ends here, likely due to an incomplete sentence or missing information.) -1 At space velocity, the highest yield of MGA was 90.2%, the conversion rate of DMO was 97.8%, and the selectivity of MGA was 92.2%. However, in this method, the silver content was too high, and the carrier preparation process was complex.
[0009] Currently, the process of hydrogenating dimethyl oxalate to methyl glycolate mainly employs silver-based or copper-based catalysts. When using silver catalysts, the selectivity for MGA formation from dimethyl oxalate is very high; however, silver is prone to sintering at high temperatures, resulting in poor catalyst stability and low activity at low temperatures. Copper-based catalysts exhibit high activity at higher reaction temperatures, but MGA readily forms ethylene glycol, producing numerous byproducts. Furthermore, the formation of a large amount of methanol byproduct easily leads to silicon loss from the support, resulting in rapid catalyst deactivation. Since deactivated catalysts are non-regenerable, there is a need to develop an industrially viable catalyst with high activity at low temperatures and a long catalyst lifetime. Summary of the Invention
[0010] In view of the aforementioned state of the prior art, the inventors of this invention have conducted extensive and in-depth research on catalysts for the hydrogenation of DMO to MGA, aiming to discover a catalyst capable of overcoming the aforementioned shortcomings of the prior art. The inventors have discovered that a bimetallic composite support catalyst, obtained by supporting silver and ruthenium bimetallic active components on a SiO2-ZrO2 composite support, possesses high specific surface area and high metal dispersion, enabling efficient conversion of DMO to MGA at low temperatures. It exhibits high DMO conversion and high MGA selectivity, maintaining high DMO conversion and high MGA selectivity even after 1500 h of reaction time.
[0011] One object of the present invention is to provide a bimetallic / composite supported Ag-Ru / SiO2-ZrO2 catalyst with a high specific surface area, which enables the conversion of DMO to MGA at a relatively low reaction temperature when used for the hydrogenation of DMO to MGA. While maintaining high DMO conversion and high MGA selectivity, the catalyst exhibits an ultra-long lifetime.
[0012] Another object of the present invention is to provide a method for preparing a bimetallic / composite supported catalyst. The Ag-Ru / SiO2-ZrO2 catalyst prepared by this method, when used for the hydrogenation of DMO to MGA, is able to convert DMO to MGA at reduced reaction temperatures. While maintaining high DMO conversion and high MGA selectivity, this catalyst exhibits an ultra-long lifetime.
[0013] A final objective of this invention is to provide a method for preparing MGA from DMO by hydrogenation using the catalyst of this invention. This method achieves high DMO conversion and high MGA selectivity at relatively low reaction temperatures and pressures, while maintaining high stability.
[0014] The embodiments for achieving the above-mentioned objectives of the present invention can be summarized as follows:
[0015] 1. A catalyst, particularly a catalyst for the production of methyl glycolate, comprising a composite support SiO2-ZrO2 and a bimetallic active component silver-ruthenium supported on the composite support, wherein the catalyst has a specific surface area of 100-1000 m². 2 / g, preferably 150-700m 2 / g, more preferably 300-500m 2 / g.
[0016] 2. The catalyst according to embodiment 1, wherein the pore volume of the catalyst is 0.1-2.5 cm. 3 / g, preferably 0.2-2.0cm 3 / g, more preferably 0.4-1.5cm 3 / g, and / or pore size of 1-100nm, preferably 2-50nm, more preferably 3-20nm.
[0017] 3. The catalyst according to embodiment 1 or 2, wherein the content of the composite support is 65-97% by weight, preferably 80-92% by weight, more preferably 85-90% by weight, and the content of the bimetallic active component is 3-35% by weight, preferably 8-20% by weight, more preferably 10-15% by weight, all based on the total weight of the catalyst.
[0018] 4. The catalyst according to any one of embodiments 1-3, wherein the ZrO2 / (SiO2+ZrO2) content in the composite support is 3-95% by weight, preferably 5-70% by weight, more preferably 5-50% by weight.
[0019] 5. The catalyst according to any one of embodiments 1-4, wherein the Ag / (Ag+Ru) content is 5-95% by weight, preferably 20-80% by weight, more preferably 30-75% by weight.
[0020] 6. A method for preparing a catalyst according to any one of embodiments 1-5, comprising the following steps:
[0021] (1) Add silicon-based materials and zirconium-based materials to water, add a slow-release agent, stir, and obtain a homogeneous mixture;
[0022] (2) Dissolve silver salt and ruthenium salt in water to prepare a bimetallic solution;
[0023] (3) Mix the homogeneous mixture obtained in step (1) with the bimetallic solution obtained in step (2), add a precipitant, and then evaporate to obtain a viscous substance; and
[0024] (4) Washing, drying, optionally tableting, calcining, optionally crushing and optionally sieving the viscous material obtained in step (3).
[0025] 7. The method according to embodiment 6, wherein the silver salt is a soluble nitrate, hydrofluoric acid salt, or organic acid salt, preferably a nitrate, and / or the ruthenium salt is a soluble nitrate, hydrochloride salt, sulfate salt, carbonate salt, or organic acid salt, preferably a soluble nitrate, more preferably ruthenium nitrite nitrate.
[0026] 8. The method according to embodiment 6 or 7, wherein the sustained-release agent is ammonium chloride, ammonium acetate, urea or ethanol.
[0027] 9. A method for preparing methyl glycolate, the method comprising, under hydrogenation reaction conditions, contacting dimethyl oxalate with hydrogen gas to carry out a hydrogenation reaction in the presence of a catalyst prepared according to any one of embodiments 1-5 or a catalyst prepared according to any one of embodiments 6-8.
[0028] 10. The method according to embodiment 9, wherein the hydrogenation reaction conditions include: a liquid hourly space velocity (LHSV) of dimethyl oxalate of 0.01-10 g / g. 催化剂 The hydrogenation reaction is carried out at a temperature of 100-300℃ and a pressure of 0.1-15 MPa, with a molar ratio of hydrogen to dimethyl oxalate of 10:1-250:1; preferably, the liquid hourly space velocity (LHSV) of dimethyl oxalate is 0.5-8 g / g. 催化剂 The hydrogenation reaction temperature is 130-210℃, the hydrogenation reaction pressure is 1-5MPa, and the molar ratio of hydrogen to dimethyl oxalate is 20:1-100:1. Detailed Implementation
[0029] According to a first aspect of the invention, a bimetallic / composite supported catalyst is provided, the catalyst comprising a composite support and a bimetallic active component supported on the support.
[0030] The bimetallic / composite supported catalyst of this invention is a supported catalyst.
[0031] The support in this invention is a silicon-based-zirconium-based composite support. Based on the total weight of the catalyst, the content of the composite support is typically 65-97% by weight, preferably 80-92% by weight, and more preferably 85-90% by weight. The ZrO2 / (SiO2+ZrO2) content in the composite support is 3-95% by weight, preferably 5-70% by weight, and more preferably 5-50% by weight.
[0032] In the catalyst of the present invention, the bimetallic active component is mainly distributed within the pores of the support. Based on the total weight of the catalyst, the content of the bimetallic active component, calculated elementally, is typically 3-35% by weight, preferably 8-20% by weight, and more preferably 10-15% by weight. In the catalyst of the present invention, the Ag / (Ag+Ru) content is 5-95% by weight, preferably 20-80% by weight, and more preferably 30-75% by weight.
[0033] In one embodiment of the present invention, the catalyst has a specific surface area of 100-1000 m². 2 / g, preferably 150-700m 2 / g, more preferably 300-500m 2 / g. In a preferred embodiment of the invention, the catalyst has a pore volume of 0.1-2.5 cm³. 3 / g, preferably 0.2-2.0cm 3 / g, more preferably 0.4-1.5cm 3 / g. In another preferred embodiment of the invention, the pore size is 1-100nm, preferably 2-50nm, and more preferably 3-20nm.
[0034] The inventors have discovered that adding a second support component to a silicon-based support can successfully suppress desilication and silver aggregation, thereby improving the catalyst's lifespan.
[0035] According to a second aspect of the present invention, a method for preparing the catalyst of the present invention is provided, comprising the following steps:
[0036] (1) Add silicon-based materials and zirconium-based materials to water, add a slow-release agent, stir, and obtain a homogeneous mixture;
[0037] (2) Dissolve silver salt and ruthenium salt in water to prepare a bimetallic solution;
[0038] (3) Mix the homogeneous mixture obtained in step (1) with the bimetallic solution obtained in step (2), add a precipitant, and then evaporate to obtain a viscous substance; and
[0039] (4) Washing, drying, optionally tableting, calcining, optionally crushing and optionally sieving the viscous material obtained in step (3).
[0040] According to the present invention, in step (1), the method of adding the catalyst support material to water (preferably deionized water) is conventional. For example, the support material can be added to water at 5-55°C (preferably room temperature (25°C)) and under stirring conditions to form a homogeneous mixture.
[0041] In step (1) of the present invention, there are no special requirements for the amount of water used. The amount of water can be 100-2000% by weight, preferably 150-1500% by weight, all based on the total weight of the carrier material.
[0042] In one embodiment of the present invention, the silicon-based material in step (1) may be solid silicon oxide powder, silica sol, or silicate ester. The zirconium-based material may be zirconium oxide powder, tetrabutyl zirconate, or zirconium nitrate.
[0043] In step (1), after the carrier material is added to the water, a slow-release agent is added. It is advantageous to use ammonium chloride, ammonium acetate, urea or ethanol as the slow-release agent for this step.
[0044] For example, in preferred step (1), all materials are added under stirring, such as mechanical stirring, to ensure uniform and stable distribution. Generally, the reaction mixture is stirred for 5-120 minutes at a stirring speed of 50-600 rpm to ensure that the resulting mixture is sufficiently uniform and stable.
[0045] According to the present invention, in step (2), the bimetallic salt is dissolved in water (preferably deionized water) to obtain a bimetallic salt solution.
[0046] The silver salt is a soluble nitrate, hydrofluoric acid salt, or organic acid salt, preferably a nitrate. The ruthenium salt is a soluble nitrate, hydrochloride salt, sulfate salt, carbonate salt, or organic acid salt, preferably a soluble nitrate, and more preferably ruthenium nitrosyl nitrate.
[0047] According to the present invention, in step (3), the homogeneous mixture obtained in step (1) is mixed with the bimetallic solution obtained in step (2), and then a precipitant is added to obtain a viscous substance.
[0048] In one embodiment of the invention, the precipitant comprises ammonia and ammonium salts or mixtures thereof, preferably ammonia and ammonium salts, more preferably ammonia water, ammonium nitrate and ammonium carbonate.
[0049] To ensure a more thorough and uniform distribution of the metal within the pores of the carrier, it is generally advantageous to stir the resulting mixture at 20-80°C for 20-120 min after mixing the homogeneous mixture obtained in step (1) with the bimetallic solution obtained in step (2) and adding the precipitant. More advantageously, after mixing the homogeneous mixture obtained in step (1) with the bimetallic solution obtained in step (2) and adding the precipitant, the resulting mixture is stirred at 30-70°C for 30-60 min.
[0050] In a preferred embodiment of the invention, ammonia water is added as a precipitant. The resulting mixture is then subjected to ammonia stripping to remove the ammonia water and leave the metallic component within the channels. The conditions for ammonia stripping are not particularly limited, but preferably include: a stripping temperature of 50-130°C and a stripping time of 0.5-50 hours. More preferably, the stripping temperature is 60-120°C and the stripping time is 2-48 hours. Particularly preferred are a stripping temperature of 80-110°C and a stripping time of 2-12 hours. Ammonia stripping can be carried out under stirring, such as mechanical stirring, at a speed of 200-600 rpm. After ammonia stripping, a viscous substance is obtained.
[0051] According to the present invention, in step (4), the viscous material obtained in step (3) is subjected to washing, drying, optionally tableting, calcining, optionally crushing and optionally sieving.
[0052] The present invention does not have any particular restrictions on the washing in step (4). Usually, water washing is used once or multiple times until the washing solution is neutral.
[0053] The present invention does not impose any particular limitation on the drying conditions in step (4). Preferably, the drying conditions include: a drying temperature of 50-160°C and a drying time of 3-48 hours. More preferably, the drying temperature is 60-150°C and the drying time is 6-24 hours. Particularly preferably, the drying temperature is 100-150°C and the drying time is 6-20 hours. The present invention does not impose any particular limitation on the drying method in step (4). For example, ordinary heating drying, microwave drying, and / or spray drying can be used, with spray drying being preferred.
[0054] In step (4), a roasting step is performed. The roasting temperature can be 150-800℃, and the roasting time can be 1-12 hours. Preferably, the roasting temperature is 200-600℃, and the roasting time is 2-10 hours. More preferably, the roasting temperature is 250-500℃, and the roasting time is 3-6 hours.
[0055] In step (4) of the method of the present invention, the dried material is optionally shaped according to conventional methods before calcination. The shaping method may be, for example, tableting, balling, or extrusion molding, in which case a binder may optionally be added to facilitate processing.
[0056] In one embodiment of the present invention, the catalyst obtained in step (4) can also be further shaped after crushing to form the desired molded body. During the molding process, a binder can be added depending on the ease of molding and the required strength of the catalyst. Generally, the catalyst obtained in step (4) is crushed, mixed with a binder, ground, and then compressed into tablets to obtain catalyst tablets. If catalyst particles are desired, the obtained catalyst tablets can also be crushed and sieved.
[0057] According to a final aspect of the present invention, a method for preparing methyl glycolate is provided, the method comprising, in the presence of the composite support catalyst of the present invention, contacting dimethyl oxalate with hydrogen gas to carry out a hydrogenation reaction under hydrogenation reaction conditions.
[0058] According to the preparation method of the present invention, the hydrogenation reaction conditions may include: a liquid hourly space velocity (LISH) of dimethyl oxalate of 0.01-10 g / g. 催化剂 The hydrogenation reaction is carried out at a temperature of 100-300℃ and a pressure of 0.1-15 MPa, with a molar ratio of hydrogen to dimethyl oxalate of 10:1-250:1. Preferably, the liquid hourly space velocity (LHSV) of dimethyl oxalate is 0.5-8 g / g. 催化剂 The hydrogenation reaction temperature is 130-210℃, the hydrogenation reaction pressure is 1-5MPa, and the molar ratio of hydrogen to dimethyl oxalate is 20:1-100:1.
[0059] If the bimetallic / composite supported catalyst of the present invention is not yet activated, it needs to be hydrogenated before being used to catalyze the hydrogenation of dimethyl oxalate to methyl glycolate. The conditions for hydrogenation reduction are conventional. Generally, the reducing gas is hydrogen or a mixture containing hydrogen and a gas inert to the reduction reaction. The reduction temperature is typically 100-300°C, preferably 150-250°C. The reduction time is typically 2-48 hours, preferably 3-24 hours.
[0060] The hydrogenation of dimethyl oxalate to methyl glycolate according to the present invention can be carried out in any reactor capable of achieving the above-described reaction conditions, such as a fixed-bed reactor, a fluidized-bed reactor, or a slurry-bed reactor, preferably in a fixed-bed reactor.
[0061] By using the catalyst of this invention to catalyze the hydrogenation of DMO to synthesize methyl glycolate, high DMO conversion and high MGA selectivity can be achieved at low temperature and low pressure.
[0062] Example
[0063] The present invention will now be described in detail with reference to embodiments and comparative examples, but the scope of the present invention is not limited to these embodiments.
[0064] In the following examples and comparative examples, gas chromatography was used to analyze the components in the system, and quantification was performed using the correction and normalization method.
[0065] N2 physical adsorption was analyzed using a Micromeritics ASAP 2020 at -196℃ (liquid nitrogen temperature) to determine parameters such as specific surface area, pore volume, and average pore size of the catalyst. First, the catalyst sample was pretreated at 300℃ to 70 mmHg under vacuum for 6 hours to remove trace amounts of water and impurities adsorbed on the catalyst surface. Then, the adsorption-desorption isotherms were measured using a static method. The specific surface area of the catalyst was calculated using BET (Bnmauer-Emmet-Teller) theory combined with the adsorption isotherms; the pore volume was obtained using BJH (Barrett-Joyner-Halenda) theory and the desorption isotherms; and the average pore size was determined using BJH (Barrett-Joyner-Halenda) theory.
[0066] The content of each component of the catalyst was determined by ICP.
[0067] Example 1
[0068] 1. Catalyst preparation:
[0069] (1) Weigh 20g of silicon powder A380 (EVONIK, Germany) and 7.8g of tetrabutyl zirconate (Kanto Chemical, Japan), dissolve them in 200mL of deionized water, add 4g of urea, and stir for 120 minutes at room temperature (i.e., 25℃, the same below) and stirring speed of 150rpm to obtain the carrier mixture.
[0070] (2) At room temperature and in the dark, dissolve 2.75g of silver nitrate and 2.4g of ruthenium nitrite (Kanto Chemical, Japan) in 300mL of water.
[0071] (3) The carrier mixture obtained in step (1) and the bimetallic salt solution obtained in step (2) were mixed at room temperature and with stirring. Then, 80g of 28% ammonia water was added at a temperature of 30°C and a stirring speed of 600rpm and stirred for 30 minutes. Then, ammonia was evaporated at 85°C and stirred at 300rpm for 3 hours to form a viscous substance.
[0072] (4) The viscous substance obtained in step (3) is washed with deionized water until the washing solution is neutral, and then dried at 120°C for 12 hours to obtain bimetallic / composite support powder, totaling 28g. The obtained bimetallic / composite support powder is pressed into tablets, calcined, crushed and sieved to obtain particulate catalyst with a particle size of 20-40 mesh, namely bimetallic / composite support catalyst Ag-Ru / SiO2-ZrO2-1.
[0073] The specific surface area of the obtained catalyst was measured to be 410.25 m². 2 / g, pore volume is 0.83cm 3 / g, with an average pore size of 7.82nm, and silver content in the catalyst is 7 wt% based on elemental silver. Ruthenium content in the catalyst is 3 wt% based on elemental ruthenium. Silicon content in the catalyst is 80 wt% based on silicon oxide, and zirconium content in the catalyst is 10 wt% based on zirconium oxide.
[0074] 2. Evaluation of the catalyst:
[0075] 1.5 ml of the catalyst particles prepared above was placed in a vertical fixed-bed reactor with an inner diameter of 10 mm and a height of 40 cm. Before reaction evaluation, the catalyst was reduced under the following conditions: a mixed gas of 15 vol% H2 and 85 vol% N2 flowed from the top of the reactor through the catalyst bed at a flow rate of 120 ml / min and exited from the bottom of the reactor; the reduction temperature was 200 °C; and the reduction time was 12 hours. After reduction, the reducing gas was replaced with pure hydrogen, the reaction system pressure was increased to 1.5 MPa, the catalyst bed temperature was reduced to 150 °C, and a 20 wt% methanol solution of DMO was introduced. Hydrogen and dimethyl oxalate were mixed before entering the reactor. The solution then entered the tubular reactor from the top, and after reaction, the product was discharged from the bottom of the reactor. The reaction conditions were as follows: the molar ratio of hydrogen to dimethyl oxalate (DMO) was 40:1, the liquid hourly space velocity of DMO was 2.0 g / ml·h, the reaction temperature was 150℃, and the reaction pressure was 1.5 MPa. Samples were taken for analysis after 3 hours of reaction to determine the conversion rate and product distribution of DMO. The reaction results are shown in Table 1.
[0076] Example 2
[0077] 1. Catalyst preparation:
[0078] The process is basically the same as in Example 1, except that the amount of silicon powder A380 added in step (1) is changed from 20g to 17g and the amount of tetrabutyl zirconate is changed from 7.8g to 15.2g.
[0079] The changes in the feed in step (2) are as follows: silver nitrate is changed from 2.75g to 2.7g and ruthenium nitrite nitrate is changed from 2.4g to 2.3g, finally obtaining Ag-Ru / SiO2-ZrO2-2 catalyst.
[0080] The specific surface area of the obtained catalyst was measured to be 439.14 m². 2 / g, pore volume 0.93cm 3 / g, with an average pore size of 8.9nm, and silver content in the catalyst is 7 wt% based on elemental silver. Ruthenium content in the catalyst is 3 wt% based on elemental ruthenium. Silicon content in the catalyst is 70 wt% based on silicon oxide, and zirconium content in the catalyst is 20 wt% based on zirconium oxide.
[0081] 2. Evaluation of the catalyst:
[0082] The catalyst was evaluated similarly to that in Example 1. The reaction results are shown in Table 1.
[0083] Example 3
[0084] 1. Catalyst preparation:
[0085] The method is basically the same as in Example 1, except that in step (1), the amount of silicon powder A380 is changed from 20g to 14.5g and the amount of tetrabutyl zirconate is changed from 7.8g to 12.5g.
[0086] The changes in the feed in step (2) are as follows: silver nitrate is changed from 2.75g to 2.7g and ruthenium nitrite nitrate is changed from 2.4g to 2.3g, finally obtaining Ag-Ru / SiO2-ZrO2-3 catalyst.
[0087] The specific surface area of the obtained catalyst was measured to be 458.8 m². 2 / g, pore volume is 0.89cm 3 / g, with an average pore size of 7.71nm, and silver content in the catalyst is 7 wt% based on elemental silver. Ruthenium content in the catalyst is 3 wt% based on elemental ruthenium. Silicon content in the catalyst is 60 wt% based on silicon oxide, and zirconium content in the catalyst is 30 wt% based on zirconium oxide.
[0088] 2. Evaluation of the catalyst:
[0089] The catalyst was evaluated similarly to that in Example 1. The reaction results are shown in Table 1.
[0090] Example 4
[0091] 1. Catalyst preparation:
[0092] The process is basically the same as in Example 1, except that in step (1), the amount of silicon powder A380 is changed from 20g to 22.0g and the amount of tetrabutyl zirconate is changed from 7.8g to 4.0g.
[0093] The changes in the feed in step (2) are as follows: silver nitrate is changed from 2.75g to 2.85g and ruthenium nitrite nitrate is changed from 2.4g to 2.43g, finally obtaining Ag-Ru / SiO2-ZrO2-4 catalyst.
[0094] The specific surface area of the obtained catalyst was measured to be 384.95 m².2 / g, pore volume 0.92cm 3 / g, with an average pore size of 9.55nm, and silver content in the catalyst is 7 wt% based on elemental silver. Ruthenium content in the catalyst is 3 wt% based on elemental ruthenium. Silicon content in the catalyst is 85 wt% based on silicon oxide, and zirconium content in the catalyst is 5 wt% based on zirconium oxide.
[0095] 2. Evaluation of the catalyst:
[0096] The catalyst was evaluated similarly to that in Example 1. The reaction results are shown in Table 1.
[0097] Example 5
[0098] 1. Catalyst preparation:
[0099] The process is basically the same as in Example 1, except that in step (1), the amount of silicon powder A380 is changed from 20g to 18.0g and the amount of tetrabutyl zirconate is changed from 7.8g to 7.0g.
[0100] The changes in the feed in step (2) are as follows: silver nitrate is changed from 2.75g to 2.14g and ruthenium nitrite nitrate is changed from 2.4g to 2.85g, finally obtaining Ag-Ru / SiO2-ZrO2-5 catalyst.
[0101] The specific surface area of the obtained catalyst was measured to be 402.71 m². 2 / g, pore volume is 0.68cm³ 3 / g, with an average pore size of 6.72nm, and silver content in the catalyst is 6 wt% based on elemental silver. Ruthenium content in the catalyst is 4 wt% based on elemental ruthenium. Silicon content in the catalyst is 80 wt% based on silicon oxide, and zirconium content in the catalyst is 10 wt% based on zirconium oxide.
[0102] 2. Evaluation of the catalyst:
[0103] The catalyst was evaluated similarly to that in Example 1. The reaction results are shown in Table 1.
[0104] Example 6
[0105] 1. Catalyst preparation:
[0106] The process is basically the same as in Example 1, except that in step (1), the amount of silicon powder A380 is changed from 20g to 18.0g and the amount of tetrabutyl zirconate is changed from 7.8g to 7.0g.
[0107] The changes in the feed in step (2) are as follows: silver nitrate is changed from 2.75g to 1.80g and ruthenium nitrite nitrate is changed from 2.4g to 3.60g, finally obtaining Ag-Ru / SiO2-ZrO2-6 catalyst.
[0108] The specific surface area of the obtained catalyst was measured to be 384.06 m². 2 / g, pore volume is 0.89cm 3 / g, with an average pore size of 9.22nm, and silver content in the catalyst is 5% by weight (based on elemental silver). Ruthenium content in the catalyst is 5% by weight (based on elemental ruthenium). Silicon content in the catalyst is 80% by weight (based on silicon oxide), and zirconium content in the catalyst is 10% by weight (based on zirconium oxide).
[0109] 2. Evaluation of the catalyst:
[0110] The catalyst was evaluated similarly to that in Example 1. The reaction results are shown in Table 1.
[0111] Example 7
[0112] 1. Catalyst preparation:
[0113] The process is basically the same as in Example 1, except that in step (1), the amount of silicon powder A380 is changed from 20g to 18.0g and the amount of tetrabutyl zirconate is changed from 7.8g to 7.0g.
[0114] The changes in the feed in step (2) are as follows: silver nitrate is changed from 2.75g to 1.42g and ruthenium nitrite nitrate is changed from 2.4g to 4.24g, finally obtaining Ag-Ru / SiO2-ZrO2-7 catalyst.
[0115] The specific surface area of the obtained catalyst was measured to be 365.37 m². 2 / g, pore volume is 0.83cm 3 / g, with an average pore size of 9.11nm, and silver content in the catalyst is 4 wt% based on elemental silver. Ruthenium content in the catalyst is 6 wt% based on elemental ruthenium. Silicon content in the catalyst is 80 wt% based on silicon oxide, and zirconium content in the catalyst is 10 wt% based on zirconium oxide.
[0116] 2. Evaluation of the catalyst:
[0117] The catalyst was evaluated similarly to that in Example 1. The reaction results are shown in Table 1.
[0118] Comparative Example 1
[0119] 1. Catalyst preparation:
[0120] The process is basically the same as in Example 1, except that the feed in step (1) is changed to 2.0g of silicon powder A3802 and 0g of tetrabutyl zirconate.
[0121] In step (2), the feed was changed to 2.69 g of silver nitrate and 2.3 g of ruthenium nitrite nitrate, and finally Ag-Ru / SiO2-A1 catalyst was obtained.
[0122] The specific surface area of the obtained catalyst was measured to be 295.82 m². 2 / g, pore volume 0.57cm 3 / g, with an average pore size of 7.67nm, and silver content in the catalyst is 7 wt% based on elemental silver. Ruthenium content in the catalyst is 3 wt% based on elemental ruthenium. Silicon content in the catalyst is 90 wt% based on silicon oxide, and zirconium content in the catalyst is 0 wt% based on zirconium oxide.
[0123] 2. Evaluation of the catalyst:
[0124] The catalyst was evaluated similarly to that in Example 1. The reaction results are shown in Table 1.
[0125] Comparative Example 2
[0126] 1. Catalyst preparation:
[0127] The process is basically the same as in Example 1, except that the feed in step (1) is changed to 20.0g of silicon powder A380 and 7.8g of tetrabutyl zirconate;
[0128] In step (2), the feed was changed to 3.95 g of silver nitrate and 0 g of ruthenium nitrite nitrate, and finally Ag / SiO2-ZrO2-A2 catalyst was obtained.
[0129] The specific surface area of the obtained catalyst was determined to be 330.5 m². 2 / g, pore volume 0.60cm 3 / g, with an average pore size of 7.28nm, and silver content in the catalyst is 10 wt% based on elemental silver. Ruthenium content in the catalyst is 0 wt% based on elemental ruthenium. Silicon content in the catalyst is 80 wt% based on silicon oxide, and zirconium content in the catalyst is 10 wt% based on zirconium oxide.
[0130] 2. Evaluation of the catalyst:
[0131] The catalyst was evaluated similarly to that in Example 1. The reaction results are shown in Table 1.
[0132] Comparative Example 3
[0133] 1. Catalyst preparation:
[0134] The process is basically the same as in Example 1, except that the feed in step (1) is changed to 1.0g of silicon powder A3802 and 7.9g of tetrabutyl zirconate;
[0135] In step (2), the feed was changed to 0g of silver nitrate and 5.6g of ruthenium nitrite nitrate, and finally Ru / SiO2-ZrO2-A3 catalyst was obtained.
[0136] The specific surface area of the obtained catalyst was measured to be 307.17 m². 2 / g, pore volume is 0.61cm 3 / g, with an average pore size of 7.95nm, and ruthenium content in the catalyst is 7 wt% (based on elemental ruthenium). Silicon content in the catalyst is 83 wt% (based on silicon oxide), and zirconium content in the catalyst is 10 wt% (based on zirconium oxide).
[0137] 2. Evaluation of the catalyst:
[0138] The catalyst was evaluated similarly to that in Example 1. The reaction results are shown in Table 1.
[0139] Comparative Example 4
[0140] 1. Catalyst preparation:
[0141] The process is basically the same as in Example 1, except that the feed in step (1) is changed to 20.0g of silicon powder A380 and 7.8g of tetrabutyl zirconate;
[0142] In step (2), the feed was changed to 24.0g of copper nitrate trihydrate and 0g of ruthenium nitrite nitrate trihydrate, and finally Cu / SiO2-ZrO2-A4 catalyst was obtained.
[0143] The specific surface area of the obtained catalyst was measured to be 303.36 m². 2 / g, pore volume 0.54cm 3 / g, with an average pore size of 7.1nm, and copper content in the catalyst is 20% by weight (based on elemental copper). Zirconium content in the catalyst is 10% by weight (based on zirconium oxide).
[0144] 2. Evaluation of the catalyst:
[0145] The catalyst was evaluated similarly to that in Example 1. The reaction results are shown in Table 1.
[0146] Comparative Example 5
[0147] 1. Catalyst preparation:
[0148] The process is basically the same as in Example 1, except that the feed in step (1) is changed to 24.0g of silicon powder A380 and 0g of tetrabutyl zirconate;
[0149] In step (2), the feed was changed to 0g of silver nitrate and 5.6g of ruthenium nitrite nitrate, and finally Ru / SiO2-A5 catalyst was obtained.
[0150] The specific surface area of the obtained catalyst was determined to be 292.3 m². 2 / g, pore volume 0.50cm 3 / g, with an average pore size of 6.9nm, and ruthenium content in the catalyst is 7% by weight (based on elemental ruthenium). Silicon content in the catalyst is 93% by weight (based on silicon oxide).
[0151] 2. Evaluation of the catalyst:
[0152] The catalyst was evaluated similarly to that in Example 1. The reaction results are shown in Table 1.
[0153] Example 8
[0154] 1. Catalyst preparation:
[0155] The process is basically the same as in Example 1, except that in step (1), 4g of urea is replaced with 4g of ammonium acetate, and the Ag-Ru / SiO2-ZrO2-8 catalyst is finally obtained.
[0156] The specific surface area of the obtained catalyst was measured to be 417.49 m². 2 / g, pore volume is 0.73cm 3 / g, with an average pore size of 7.02nm, and silver content in the catalyst is 7 wt% based on elemental silver. Ruthenium content in the catalyst is 3 wt% based on elemental ruthenium. Silicon content in the catalyst is 80 wt% based on silicon oxide, and zirconium content in the catalyst is 10 wt% based on zirconium oxide.
[0157] 2. Evaluation of the catalyst:
[0158] The catalyst was evaluated similarly to that in Example 1. The reaction results are shown in Table 1.
[0159] Example 9
[0160] 1. Catalyst preparation:
[0161] The process is basically the same as in Example 1, except that in step (3), ammonia is replaced with 40g of ammonium nitrate, ultimately yielding the Ag-Ru / SiO2-ZrO2-9 catalyst.
[0162] The specific surface area of the obtained catalyst was measured to be 413.2 m². 2 / g, pore volume is 0.68cm³ 3 / g, with an average pore size of 6.62nm, and silver content in the catalyst is 7 wt% based on elemental silver. Ruthenium content in the catalyst is 3 wt% based on elemental ruthenium. Silicon content in the catalyst is 80 wt% based on silicon oxide, and zirconium content in the catalyst is 10 wt% based on zirconium oxide.
[0163] 2. Evaluation of the catalyst:
[0164] The catalyst was evaluated similarly to that in Example 1. The reaction results are shown in Table 1.
[0165] Example 10
[0166] 1. Catalyst preparation:
[0167] The process is basically the same as in Example 1, except that in step (3), 80g of 28% ammonia water is replaced with 40g of ammonium carbonate, ultimately yielding the Ag-Ru / SiO2-ZrO2-10 catalyst.
[0168] The specific surface area of the obtained catalyst was measured to be 428.2 m². 2 / g, pore volume is 0.84cm 3 / g, with an average pore size of 7.88nm, and silver content in the catalyst is 7 wt% based on elemental silver. Ruthenium content in the catalyst is 3 wt% based on elemental ruthenium. Silicon content in the catalyst is 80 wt% based on silicon oxide, and zirconium content in the catalyst is 10 wt% based on zirconium oxide.
[0169] 2. Evaluation of the catalyst:
[0170] The catalyst was evaluated similarly to that in Example 1. The reaction results are shown in Table 1.
[0171] Table 1
[0172]
[0173] Example 11
[0174] 1. Catalyst preparation:
[0175] The catalyst from Example 1 was used.
[0176] 2. Evaluation of the catalyst:
[0177] The catalyst was evaluated similarly to that in Example 1, under the same reaction conditions but with an extended reaction time. At 1500 h, the conversion of DMO was 90.13%, and the selectivity for MGA was 94.93%.
[0178] Example 12
[0179] 1. Catalyst preparation:
[0180] The catalyst from Example 4 was used.
[0181] 2. Evaluation of the catalyst:
[0182] The catalyst was evaluated similarly to that in Example 4, under the same reaction conditions but with an extended reaction time. At 1500 h, the conversion of DMO was 91.07%, and the selectivity for MGA was 93.77%.
[0183] Example 13
[0184] 1. Catalyst preparation:
[0185] The catalyst from Example 7 was used.
[0186] 2. Evaluation of the catalyst:
[0187] The catalyst was evaluated similarly to that in Example 7, under the same reaction conditions but with an extended reaction time. At 1500 h, the conversion of DMO was 92.54%, and the selectivity for MGA was 93.69%.
[0188] Comparative Example 6
[0189] 1. Catalyst preparation:
[0190] The catalyst used was from Comparative Example 5.
[0191] 2. Evaluation of the catalyst:
[0192] The catalyst was evaluated similarly to that in Comparative Example 5, under the same reaction conditions but with an extended reaction time. At 150 h, the conversion rate of DMO was 69.22%, and the selectivity for MGA was 44.32%.
Claims
1. A catalyst for the preparation of methyl glycolate, comprising a composite support SiO2-ZrO2 and a bimetallic active component silver-ruthenium supported on the composite support, wherein the catalyst has a specific surface area of 100-1000 m². 2 / g, wherein the catalyst is prepared by a method comprising the following steps: (1) Add silicon-based materials and zirconium-based materials to water, add a slow-release agent, stir, and obtain a homogeneous mixture; (2) Dissolve silver salt and ruthenium salt in water to prepare a bimetallic solution; (3) Mix the homogeneous mixture obtained in step (1) with the bimetallic solution obtained in step (2), add a precipitant, and then evaporate to obtain a viscous substance; and (4) The steps of washing, drying, optionally pressing, calcining, optionally crushing and optionally sieving the viscous material obtained in step (3).
2. The catalyst according to claim 1, wherein the specific surface area of the catalyst is 150-700 m². 2 / g.
3. The catalyst according to claim 1, wherein the specific surface area of the catalyst is 300-500 m². 2 / g.
4. The catalyst according to claim 1, wherein the pore volume of the catalyst is 0.1-2.5 cm. 3 / g, and / or pore size of 1-100nm.
5. The catalyst according to claim 4, wherein the pore volume of the catalyst is 0.2-2.0 cm³. 3 / g.
6. The catalyst according to claim 4, wherein the pore volume of the catalyst is 0.4-1.5 cm. 3 / g.
7. The catalyst according to claim 4, wherein the pore size of the catalyst is 2-50 nm.
8. The catalyst according to claim 4, wherein the pore size of the catalyst is 3-20 nm.
9. The catalyst according to any one of claims 1-8, wherein the content of the composite support is 65-97% by weight, and the content of the bimetallic active component is 3-35% by weight, based on the total weight of the catalyst.
10. The catalyst according to claim 9, wherein the content of the composite support is 80-92% by weight, based on the total weight of the catalyst.
11. The catalyst according to claim 9, wherein the content of the composite support is 85-90% by weight, based on the total weight of the catalyst.
12. The catalyst according to claim 9, wherein the content of the bimetallic active component is 8-20% by weight, based on the total weight of the catalyst.
13. The catalyst according to claim 9, wherein the content of the bimetallic active component is 10-15% by weight, based on the total weight of the catalyst.
14. The catalyst according to any one of claims 1-8 and 10-13, wherein the ZrO2 / (SiO2+ZrO2) content in the composite support is 3-95% by weight.
15. The catalyst according to claim 9, wherein the ZrO2 / (SiO2+ZrO2) content in the composite support is 3-95% by weight.
16. The catalyst according to claim 14, wherein the ZrO2 / (SiO2+ZrO2) content in the composite support is 5-70% by weight.
17. The catalyst according to claim 15, wherein the ZrO2 / (SiO2+ZrO2) content in the composite support is 5-70% by weight.
18. The catalyst according to claim 14, wherein the ZrO2 / (SiO2+ZrO2) content in the composite support is 5-50% by weight.
19. The catalyst according to claim 15, wherein the ZrO2 / (SiO2+ZrO2) content in the composite support is 5-50% by weight.
20. The catalyst according to any one of claims 1-8, 10-13 and 15-19, wherein the Ag / (Ag+Ru) content is 5-95% by weight.
21. The catalyst according to claim 20, wherein the Ag / (Ag+Ru) content is 20-80% by weight.
22. The catalyst according to claim 20, wherein the Ag / (Ag+Ru) content is 30-75% by weight.
23. The catalyst according to any one of claims 1-8, 10-13, 15-19 and 21-22, wherein the silver salt is a soluble nitrate, hydrofluoric acid salt and an organic acid salt, and / or the ruthenium salt is a soluble nitrate, hydrochloride salt, sulfate salt, carbonate salt and an organic acid salt.
24. The catalyst according to claim 20, wherein the silver salt is a soluble nitrate, hydrofluoric acid salt, or an organic acid salt, and / or the ruthenium salt is a soluble nitrate, hydrochloride salt, sulfate salt, carbonate salt, or organic acid salt.
25. The catalyst according to claim 23, wherein the silver salt is a soluble nitrate.
26. The catalyst according to claim 23, wherein the ruthenium salt is a soluble nitrate.
27. The catalyst according to claim 23, wherein the ruthenium salt is nitrosyl nitrate ruthenium.
28. The catalyst according to any one of claims 1-8, 10-13, 15-19, 21-22 and 24-27, wherein the slow-release agent is ammonium chloride, ammonium acetate, urea or ethanol.
29. A method for preparing methyl glycolate, the method comprising, in the presence of a catalyst according to any one of claims 1-28, contacting dimethyl oxalate with hydrogen gas under hydrogenation reaction conditions to carry out a hydrogenation reaction.
30. The method according to claim 29, wherein the hydrogenation reaction conditions include: The liquid hourly space velocity (LISH) of dimethyl oxalate is 0.01-10 g / g. 催化剂 The hydrogenation reaction is carried out at a temperature of 100-300℃ and a pressure of 0.1-15MPa, with a molar ratio of hydrogen to dimethyl oxalate of 10:1-250:
1.
31. The method according to claim 29, wherein the hydrogenation reaction conditions include: The liquid hourly space velocity (LISH) of dimethyl oxalate is 0.5-8 g / g. 催化剂 The hydrogenation reaction temperature is 130-210℃, the hydrogenation reaction pressure is 1-5MPa, and the molar ratio of hydrogen to dimethyl oxalate is 20:1-100:1.
Citation Information
Patent Citations
Catalyst for synthesizing methyl glycolate through hydrogenation by dimethyl oxalate and preparation method thereof
CN101700496B
Catalyst for synthesizing methyl glycolate by hydrogenating dimethyl oxalate as well as preparation method and application thereof
CN108620107A
Catalyst for synthesizing glycolic acid ester and preparation method and application of catalyst
CN105363438A